PENGARUH LIKUIDITAS, PROFITABILITAS DAN AKTIVITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN - Petronela Elvis Arci; Yuli Ermawati (Jurnal Ekonomi, Bisnis dan Social, 2024)
The research aims to test and analyze the influence of liquidity, profitability and activity on company value. The population used in this research is manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sample selection in this research used purposive sampling, namely through sampling criteria and resulted in 15 companies being sampled from 35 manufacturing companies in the food and beverage sub-sector for the 2019-2021 period. The analytical tool used in this research uses multiple linear regression analysis techniques using the SPSS version 25 statistical testing tool. Based on the results of data analysis using the t test, the results show that partially liquidity and profitability do not have a significant influence on company value, while activity has a positive influence. significant to company value. Meanwhile, based on the results of data analysis using the f test, simultaneously liquidity, profitability and activity have a significant influence on company value. The results of the coefficient of determination test (R2) obtained a value of 20.6%, this shows that variables, liquidity, profitability and activity have an influence on company value in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) during the 2019- 2021.